EKSISTENSI PENDIDIKAN ISLAM DI INDONESIA (Perspekstif Sejarah Pendidikan Nasional) - Umar Umar (Lembaga Pendidikan dan Tenaga Kependidikan (Center for Teacher Training) Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar in collaboration with Lecturer Consortium of Tarbiyah and Teacher Training, 2016)
The concept of Islamic education in Indonesia in fact has been ongoing since the incoming and development of Islam itself. Acceptance of Islam as a patron of life, of course offset by the process of learning to know and to understand the teachings of Islam, as well as a concrete evidence of the birth of Islamic education. In fact, it should be noted that manifestation of Islamic education as a sub system of national education has historically been important in the development of education in Indonesia. That condition is able analyzed of the existence of Islamic education during the colonial era, the time of independence, to the process of integration of Islamic education into the national education system. Thus, the development of education in Indonesia is inseparable from the existence of Islamic education that is rooted in tradition and ritualized religious muslim community in Indonesia.